Tumor microbiome metabolism: A game changer in cancer development and therapy - Zhou, Xiaozhuang; Kandalai, Shruthi; Hossain, Farzana; Zheng, Qingfei (Frontiers in Oncology, 2022)
More and more recent evidence indicates that the human microbiome plays essential roles in pathophysiological states, including cancer. The tumor microbiome, an emerging concept that has not yet been clearly defined, has been proven to influence both cancer development and therapy through complex mechanisms. Small molecule metabolites produced by tumor microbiome through unique biosynthetic pathways can easily diffuse into tissues and penetrate cell membranes through transporters or free diffusion, thus remodeling signaling pathways of cancer and immune cells by interacting with biomacromolecules. Targeting tumor microbiome metabolism could offer a novel perspective for not only understanding cancer progression, but also developing new strategies for treatment of multiple cancer types. Here, we summarize recent advances regarding the role tumor microbiome plays as a game changer in cancer biology. Specifically, the metabolites produced by the tumor microbiome and their potential effects on the cancer development therapy are discussed to understand the importance of the microbial metabolism in tumor microenvironment. Finally, the new anti-cancer therapeutic strategies that target tumor microbiome metabolism are reviewed and proposed to provide new insights in clinical applications.